Epidermoid Cyst Occurring Within an Intrapancreatic Accessory Spleen. A Case Report and Review of the Literature - Horn, Adam J; Lele, Subodh M (JOP. Journal of the Pancreas, 2011)
Context Epidermoid cysts occurring within intrapancreatic accessory spleens are exceptionally rare entities, with only 21 previously reported cases. Their clinical presentation prior to pathologic assessment can raise concern for possible malignancy; however, they behave in a benign fashion. Case report A 62-year-old male presented with complaints of abdominal pain. Imaging revealed left-sided retroperitoneal mass and surgical exploration was recommended. Surgery revealed a cystic cavity containing necrotic debris originating from the tail of the pancreas. Microscopy was consistent with an epidermoid cyst arising within an intrapancreatic accessory spleen with positive immunoperoxidase staining for CEA. Conclusion Epidermoid cysts occurring within intrapancreatic accessory spleens can mimic a malignant process both clinically and radiographically. Surgery with pathologic assessment is the only reliable means of diagnosis. While they are a very rare entity, it is an important component of a complete differential diagnosis for a patient presenting with a pancreatic tail mass. Image: Immunoperoxidase positivity for CEA in the epithelium of the cyst.